Cyclotron production of 64Cu by proton irradiation of enriched 64Ni target: Validation of Geant4 simulation parameters through experimental data - Baruta, Simona; Leonte, Radu; Cocioaba, Diana; Craciun, Liviu; Ur, Calin Alexandru; Niculae, Dana (Frontiers in Physics, 2022)
The use of radioisotopes in nuclear medicine applications became essential for the diagnosis and follow-up imaging of many oncological, cardiovascular, and neurodegenerative diseases, in a safe and non-invasive way. Their use in the personalized treatment of tumors is on the verge to change oncological patient management. Optimization of radioisotope production aims to maximize production efficiency while minimizing side reactions and costs. A practical approach to balance these non-converging ways is to employ the simulation tools in the process design phase and experimental setup. In this way, the production yield can be estimated and the radionuclide impurities content that appears during the bombardment of the target of interest can be optimally set below acceptable limits. Copper-64 is an emerging radionuclide in nuclear medicine theragnostic applications due to three decay modes, namely electron capture, electron (β-) and positron (β+) emissions, and a 12.7 h half-life, favorable for visualization of fast biological processes. Optimization of 64Cu production by irradiation of enriched 64Ni targets with protons in a particular geometry on a TR-19 cyclotron is discussed in this work. The simulated activity produced on different levels of enrichment of the 64Ni targets was calculated using the Monte Carlo simulation in the Geant4 platform, where a customized solid target irradiation system set-up was replicated; the obtained parameters were implemented in the experiments and the results were compared, aiming to validate the simulation parameters through experimental data. As the simulated and experimental results regarding the production of 64Cu via 64Ni(p,n)64Cu reaction are in good compliance, the tool can be further applied for the optimization of the production of other radionuclides on the same set-up.